Local social capital in the Philippines - Mangada, Ladylyn L. (Danyag :the UPV journal of humanities and social sciences, 2006)
"This paper explored the social capital of selected communities in Leyte, in terms of the presence of community groups and networks, collective action and cooperation, problem solving and democratic participation process of decision making and conflict management and resolution. Associational life in these communities is not vibrant and bonding social capital is dominant among existing groups. Poverty, partisan politics and bad governance caused the weakening of social connectedness while direct socioeconomic benefits drive and may help sustain the villagers' affiliation in uncoerced human association. Social cooperation and political participation among the people is being undermined by authoritarian habits of legitimate authorities and the people's dependence on local elites."